Advances and Trends in Non-conventional, Abrasive and Precision Machining - Markopoulos, Angelos P.; Deja, Mariusz (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The work included in this book pertains to advanced abrasive and nonconventional machining processes. These processes are at the forefront of modern technology, with significant practical significance. Their importance is also made clear by the case studies that are included in the research that is presented in the book, pertaining to important materials and high-end applications. However, the particularities of these manufacturing processes need to be further investigated and the processes themselves need to be optimized. This is conducted in the presented works with significant experimental and modeling work, incorporating modern tools of analysis and measurements.